Fading : 40 Belgian contemporary artists - Elias, Willem; Leblanc, Claire; Swinnen, Johan; Vanderstichelen, Sven; Museum van Elsene, Elsene (Ghent : Snoeck Publishers, 2009)
Bailly, Virginie ; Balleux, Stephan ; Benhelima, Charif ; Borremans, Michaël ; Braeckman, Dirk ; Broucke, Koen ; Bytebier, Jean-Marie ; Clarysse, Johan ; De Beul, Bert ; Delrue, Ronny ; De Maesschalck, Jan ; De Smet, Gery ; De Vliegher, Jan ; de Vos, Eddy ; Devriendt, Robert ; Dondeyne, Luc ; Ghekiere, Joris ; Gillen, Tina ; Hanssen, Karin ; Heyrman, Hugo ; Gauthier, Hubert ; Huyghe, Thomas ; Leblon, Stéphanie ; Michiels, Fred ; Michielsen, Franky ; Najd, Maryam ; Reniere & Depla ; Serneels, Stefan ; Tuymans, Luc ; Van Bossche, Guy ; van den Broek, Koen ; Vanden Eynde, Patrick ; Vanderleenen, Marc ; Vanderlinden, Carole ; Van Imschoot, Jan ; Vanriet, Jan ; Vermeersch, Pieter ; Weidenbaum, Peter ; Wouters, Karel ; Wright, Cindy
Publication on the occasion of the exhibition 'Fading: 40 Belgian contemporary artists' at the Museum van Elsene in Elsene, 25.06.2009-13.09.2009
boek